2021
DOI: 10.1111/jofi.13002
|View full text |Cite
|
Sign up to set email alerts
|

Who Wears the Pants? Gender Identity Norms and Intrahousehold Financial Decision‐Making

Abstract: Using microdata from U.S. household surveys, I document that families with a financially sophisticated husband are more likely to participate in the stock market than those with a wife of equal financial sophistication. This pattern is best explained by gender identity norms, which constrain women's influence over intrahousehold financial decision-making. A randomized controlled experiment reveals that female identity hinders idea contribution by the wife. These findings underscore the roles of intrahousehold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(18 citation statements)
references
References 127 publications
0
18
0
Order By: Relevance
“…While previous studies have increasingly focused on the interrelationship between intra-household task divisions and financial decision making (e.g. Bertrand et al, 2015;D'Acunto et al, 2020;Ke, 2021), this is the first study to show how practices induced by gender-normative roles appear to contribute to the gender wealth gap originating from differential savings goals. It becomes especially clear that in the scope of savings goals, gender attitudinal differences in pessimism, risk-aversion, or aspirations with respect to achieving long-term challenging economic outcomes, are clearly not intrinsic, but dependent on the gender-normative roles adopted by men and women within the household.…”
Section: Synthesis: Linking Qualitative With Quantitative Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…While previous studies have increasingly focused on the interrelationship between intra-household task divisions and financial decision making (e.g. Bertrand et al, 2015;D'Acunto et al, 2020;Ke, 2021), this is the first study to show how practices induced by gender-normative roles appear to contribute to the gender wealth gap originating from differential savings goals. It becomes especially clear that in the scope of savings goals, gender attitudinal differences in pessimism, risk-aversion, or aspirations with respect to achieving long-term challenging economic outcomes, are clearly not intrinsic, but dependent on the gender-normative roles adopted by men and women within the household.…”
Section: Synthesis: Linking Qualitative With Quantitative Resultsmentioning
confidence: 89%
“…Closer to the scope of this study, recent work within the household finance literature has shown how gender norms also prescribe different roles for money management and financial planning. It is for instance well documented that, concerning savings for the long run, retirement planning often remains a task associated with the husband in a couple (Ke, 2018(Ke, , 2021Noone et al, 2010). Further, Fonseca et al (2012) and Hitczenko (2016) find using survey data on US consumers, that women in a couple are more likely than men to report that they are responsible for the day-to-day budget management in the form of dealing with the household short-term financial questions, shopping and paying the bills.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations